2023
DOI: 10.1186/s40246-022-00447-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of TP53 and genes related to homologous recombination repair in breast cancer with germline BRCA1/2 mutations

Abstract: Background Germline mutations of breast cancer susceptibility gene BRCA1 and BRCA2 (gBRCA1/2) are associated with elevated risk of breast cancer in young women in Asia. BRCA1 and BRCA2 proteins contribute to genomic stability through homologous recombination (HR)-mediated double-strand DNA break repair in cooperation with other HR-related proteins. In this study, we analyzed the targeted sequencing data of Korean breast cancer patients with gBRCA1/2 mutations to investigate the alterations in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
1
3
1
Order By: Relevance
“…Therefore, it is possible that p53 dysfunction leads to a different program of genome instability in estrogen responsive tissues compared to other tissues. Other groups have shown that homologous recombination deficiency (HRD) occurs in TP53 mutated samples irrespective of HR gene alterations 49 ; however, we did not observe higher HRD in LFS-BC compared to nonLFS-BC and DNA damage response pathway were not dysregulated. This again shows that tumorigenesis follows distinct, likely tissue-specific, pathways when p53 dysfunction is the initiating event versus a later event in tumor evolution.…”
Section: Discussioncontrasting
confidence: 96%
“…Therefore, it is possible that p53 dysfunction leads to a different program of genome instability in estrogen responsive tissues compared to other tissues. Other groups have shown that homologous recombination deficiency (HRD) occurs in TP53 mutated samples irrespective of HR gene alterations 49 ; however, we did not observe higher HRD in LFS-BC compared to nonLFS-BC and DNA damage response pathway were not dysregulated. This again shows that tumorigenesis follows distinct, likely tissue-specific, pathways when p53 dysfunction is the initiating event versus a later event in tumor evolution.…”
Section: Discussioncontrasting
confidence: 96%
“…Patients with both BRCA1/2 and TP53 gene mutations were more likely to have hormone receptor negative cancers, high Ki-67 values, and increased genetic mutations, especially of hormone receptor-related genes. Survival benefits were observed in the BRCA2 mutation carrier patients with TP53 co-mutation, compared to those with TP53 wild types [63]. This valuable observation supports the increased genome stabilizer impact of mutated TP53, providing compensatory genome stabilization in tumors with BRCA2 gene mutation.…”
Section: Both Healthy Cells and Tumor Cells With Brca Mutation Show C...supporting
confidence: 56%
“…Notably, this result agrees with a recent study reporting that TP53 mutation in the background of germline BRCA2 mutation has a beneficial effect on survival. 57 …”
Section: Resultsmentioning
confidence: 99%